Satisfaction with democracy in Turkey: Findings from a national survey - Akboğa, Sema; Şahin, Osman (SAGE Publications Ltd, 2021)
A variety of factors affect citizens' satisfaction with democracy. Based on Turkey's political and economic context, as well as the existing literature, this study investigates the effect of four factors on people's satisfaction with democracy in Turkey: citizens' conceptualizations of democracy, being a political winner, citizens' perceptions of electoral integrity, and ethnic identity. Regression analysis of a nationally representative survey reveals that political losers and those with negative perceptions of electoral integrity are less satisfied with democracy in Turkey, while people's conceptualizations of democracy and ethnic identity do not have an effect on satisfaction with democracy. We conclude that, in Turkey, political polarization and negative perceptions of electoral integrity trigger a decline in citizens' satisfaction with democracy, which requires the attention of policymakers.
Keywords: Conceptualizations of Democracy; Electoral Integrity; Political Winner; Satisfaction With Democracy; Turkey